Cooling Process of Titanium Alloy Blades After Combustion Using Three Dimensional Heat Flow Coupling Numerical Simulation - LIANG Xian-ye; MI Guang-bao; LI Pei-jie; CAO Jing-xia; HUANG Xu (Cailiao gongcheng, 2018)

(untitled)
In order to understand the cooling procedure of aviation engine blade after titanium combustion, the finite element method was used to simulate the temperature and fluid field of ROTOR37 model after combustion occurred with 550℃ fire proof titanium alloy(TF550 titanium alloy) and 600℃ high temperature titanium alloy(TA29 titanium alloy), respectively. The results show that the relative mach number influences the cooling procedure of blade, the cooling performance at the area of mach number about 0.7-1 is much higher than other area; compared with the leading edge, the cooling process of the tip is more complex, and the cooling rate is an order of magnitude lower than that of the leading edge. The difference of cooling temperature between TF550 titanium alloy and TA29 titanium alloy at tip combustion area is quite observable; and the maximum value occurs within the scope of 1000-2500K; the former is more than 100K lower than the latter, the value is reduced into 30K within the scope of 300-500K. The temperature distortion of the flow field would increase the intensity of the surge, the effect of combustion on the surge margin should be fully considered during the design of the blade.